Effectiveness of comprehensive nursing intervention program (CNIP) on knowledge and practice regarding the prevention of non-insulin-dependent diabetes mellitus (NIDDM) among adults - Bhumika Koirala; Venkatesan Balu; Sonia Kamei; Yumnam Sushma Devi; Pratima Sapkota (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: There are estimated 72.96 million cases of diabetes in the adult population of India. The prevalence in urban areas ranges between 10.9% and 14.2%, and the prevalence in rural India ranges between 3.0% and 7.8% among the population aged 20 years and above with a much higher prevalence among individuals aged over 50 years. This study aimed to determine the effectiveness of comprehensive nursing intervention program (CNIP) on knowledge and practice regarding the prevention of non-insulin-dependent diabetes mellitus (NIDDM) among adults. MATERIALS AND METHODS: A quasi-experimental one-group pretest-posttest design was chosen for the study. Adults were selected using a simple random sampling technique by the lottery method; of 120 eligible adults, 60 were selected to participate in the study. The study was conducted in an urban community, Bangalore, and data were collected from March 25, 2022, to April 23, 2022. CNIP consisted of education, demonstration of exercise, and information booklet. The pretest and posttest were collected using the structured knowledge questionnaire for assessing the level of knowledge and non-observational checklist for assessing the level of practice among adults. Data were analyzed by descriptive and inferential statistics. RESULTS: There was significant improvement in the mean scores of knowledge from 52.3 to 82.2 and practice mean score from 45.5 to 68.4. The paired t-test value of knowledge was 3.88, and practice was 2.97, which was significant at P < 0.05 level. CONCLUSIONS: The study concluded that CNIP had a great role in increasing the level of knowledge and practice among adults in the prevention of NIDDM.